À l’heure de la « deuxième » mondialisation, une ville mondiale est-elle forcément une ville globale ? - Cynthia Ghorra-Gobin (Confins)
The globalization of the economy of the last three decades understood as a new phase of the capitalist system has seriously reshaped the geography of the economic production at the world scale. Anglo-American researchers were among the first to analyze the impacts of this global economy mainly (Anglo-American cities) and to identify the role of command (of some of them). They indifferently used the two following expressions “world city” and “global city” to stress the new hierarchy of cities, beyond their demographic weight. This article based on the inclusion of a historical perspective argues in favour of a distinction between these two expressions. A “global city” refers to the city integrated in global flows of capital, information and knowledge while a “world city” should refer to the contribution of any given city to the world history. Its contribution could be measured in terms of legacy, culture influence, social memory and, its capacity of attracting visitors from the rest of the world.